Improving the Yield of Rural Education Research: An Editor's Swan Song - Thodore Coladarci (Journal of Research in Rural Education, 2007)
In my 15th and final year as JRRE editor, I identify methodological and substantive shortcomings in the rural education research literature and, in turn, suggest strategies for improvement. I structure my observations around the following considerations: describing the rural context of research, making the rural argument, framing the research question, drawing on other disciplines, synthesizing the extant research, and distinguishing between (a) exploring empirical questions and (b) adducing data to support personal convictions.